1997
DOI: 10.1021/la9700836
|View full text |Cite
|
Sign up to set email alerts
|

A Small-Angle Neutron Scattering Study of Water in Carbon Dioxide Microemulsions

Abstract: Phase behavior and small angle neutron scattering (SANS) experiments were performed on mixtures of D2O/CO2/ammonium carboxylate perfluoropolyether (PFPE) surfactant as a function of pressure (192−287 bar) and D2O composition (0.8−2.0 wt %) at 35 °C. SANS measurements provided direct evidence of water-swollen inverted micelles in CO2. At a constant PFPE concentration of 2.1 wt % in CO2, the microemulsion core radius increased from 20 to 36 Å as the D2O concentration increased from 0.8 to 2.0 wt %. For a constan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
185
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(199 citation statements)
references
References 18 publications
13
185
0
1
Order By: Relevance
“…The details of surfactant synthesis, purification and characterization can be found elswhere 6 20 , and dsurfactant=1.7 g cm -3 as a typical fluorinated compound 21 . From the mass density and bound coherent scattering lengths of the isotopes, the SLD of each component can be calculated and constrained for fitting (ρsurfactant=3.5×10 -6 Å -2 , ρD2O=6.3×10 -6 Å -2 , ρCO2=1.6×10 -6 Å -2 when dCO2 =0.68 g cm -3 , and 2.3×10 -6 Å -2 when dCO2 =0.92 g cm -3 ) It should be noted that the SLD for the water cores of microemulsion droplets is varied through H2O/D2O mixing, and the actual values are noted in appropriate sections below.…”
Section: Materials and Compositionsmentioning
confidence: 99%
“…The details of surfactant synthesis, purification and characterization can be found elswhere 6 20 , and dsurfactant=1.7 g cm -3 as a typical fluorinated compound 21 . From the mass density and bound coherent scattering lengths of the isotopes, the SLD of each component can be calculated and constrained for fitting (ρsurfactant=3.5×10 -6 Å -2 , ρD2O=6.3×10 -6 Å -2 , ρCO2=1.6×10 -6 Å -2 when dCO2 =0.68 g cm -3 , and 2.3×10 -6 Å -2 when dCO2 =0.92 g cm -3 ) It should be noted that the SLD for the water cores of microemulsion droplets is varied through H2O/D2O mixing, and the actual values are noted in appropriate sections below.…”
Section: Materials and Compositionsmentioning
confidence: 99%
“…16,17 To obtain more economic and environmentally friendly W/CO2 µEs, the minimum fluorine content necessary to render a surfactant CO2-philic has been identified by using double-pentyl-tail surfactants with different fluorination levels. It was found that at least two fluorinated carbons (CF3CF2-) are required to stabilize µEs.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have been directed toward the development of a surfactant system for stable formation of a W/scCO 2 mE, and more than 150 surfactants have been examined in these studies [7][8][9][10][11][12][13][14][15][16][17][18][19] . However, only a few have succeeded in developing a W/scCO 2 mE with W 0 c > 0 (W 0 c :water-to-surfactant molar ratio corrected by subtracting the moles of water soluble in CO 2 ).…”
mentioning
confidence: 99%